Avaliação temporal da migração de neutrófilos e mediadores inflamatórios em mandíbulas de camundongos swiss tratados com ácido zoledrônico - Carmo Filho, José Ronildo Lins do (2018)
Zoledronic acid (ZA) is a third generation aminobisphosphonate that inhibits bone resorption through the induction of apoptosis and inhibition of the mevalonate pathway in cholesterol synthesis. The induction of cytokines due to their toxicity is important in the migration and activation of neutrophils, which have a shortened survival in the presence of ZA. This mechanism can induce tissue damage and increase the potential for phagocytosis and destruction of macrophages. The objective of the present work was to delineate the temporal course and mediators involved in the migration of neutrophils in jaws of mice treated with ZA. Male swiss mice (N=192) were divided into two groups: one undergoing infusion with saline solution (0.1ml/kg, e.v.) with or without exodontia, and another submitted to infusion of ZA (0.20mg/kg; e.v.) with or without exodontia. Three consecutive weekly doses of ZA or saline (D0, D7, D14) were given. After 28 days of the last administration, the left and right lower first molar (D42) was extracted. An additional dose of ZA or saline was given the following week (D49). One month after the exodontia (D70) the protocol came to an end. The animals were euthanized weekly (n=6/group) and the jaws were removed for quantification of myeloperoxidase and dosages of inflammatory mediators (IL-1β, NF-κB and TNF-α) by enzyme-linked immunosorbent assay (Elisa). The Anova/Bonferroni and chi-square tests were used for statistical analysis (p<0.05). A significant increase in MPO levels from D0 (2,20±0,09) to D7 (5,40±0,51) was observed in the groups treated with ZA (without exodontia), maintaining a plateau that showed no significant variation from D14 (6,50±,43) to D70 (8,40±0,83) (p<0.001). When submitted to the exodontia, the ZA group showed a significant increase of MPO (D42), decreasing significantly in the following week (D49) and maintaining significantly higher values (up to D70), in relation to the animals that only received ZA and did not go through procedure (p<0.001). The animals treated with ZA (without exodontia) also showed increased levels of IL-1β, NF-κB and TNF-α from D0 to D21, maintaining these values high in D42 and D56 (p<0.001). After the exodontia, these groups treated with AZ showed a significant increase of these markers in D42 with reduction in D56. Nevertheless, D56 values remained higher in relation to the basal period (D0) and after infusion of ZA in D21 (p<0.001). Chronic infusion of ZA in mice may lead to sustained inflammatory changes with increased proinflammatory markers in the mandibular bone of these animals, as well as alteration in the number of neutrophils. These alterations can be even higher and also sustained when a stimulating factor (exodontia) is associated with the infusions.